2020
DOI: 10.1088/2043-6254/ab7c56
|View full text |Cite
|
Sign up to set email alerts
|

Functionalisation of multi-walled carbon nanotubes by esterification method for poly(ethylene)glycol attachment and their characterization

Abstract: In this study, we have successfully functionalised multi-walled carbon nanotubes (MWCNT) surfaces with poly(ethylene)glycol (PEG) via an esterification method in which the oxygenated functional groups are created by chemical oxidations with a mixture of nitric acid and sulfuric acid solutions (ratio of 1:3, v/v), and then it is reacted with functional groups of PEG. Different techniques including FE-SEM, TEM, EDS, FT-IR spectrometry, Raman spectroscopy and TGA are applied to identify the characteristics of MWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The main goal of preparing oxCNTs is to obtain polar structures to avoid aggregation associated with cytotoxicity. Further functionalization of oxCNTs can introduce other functionalities through direct esterification using alcohols. This can be chosen as the best experimental condition to prepare PEG-functionalized CNTs …”
Section: Rational Design and Preparation Of Cnts-based Drug-delivery ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of preparing oxCNTs is to obtain polar structures to avoid aggregation associated with cytotoxicity. Further functionalization of oxCNTs can introduce other functionalities through direct esterification using alcohols. This can be chosen as the best experimental condition to prepare PEG-functionalized CNTs …”
Section: Rational Design and Preparation Of Cnts-based Drug-delivery ...mentioning
confidence: 99%
“…208−212 This can be chosen as the best experimental condition to prepare PEG-functionalized CNTs. 213 The chemistry for functionalization of CNTs includes methods of amidation. In particular, it was shown that the direct solvent-free amination designed by Basiuk and coworkers 214−217 facilitates oxCNTs to react with amines, avoiding organic solvents, which is ideal for applications in nanomedicine.…”
Section: Chemical Functionalization In Cnts 321 Biocompatibility By D...mentioning
confidence: 99%